(untitled) (International Journal of Nursing Education, 2021)
The Aim: The aim of this study was to evaluate the effectiveness of a training module about safety blood transfusion on nurses’ competence. Methods: Pre experimental one group pre and post-test design was adopted. The study was conducted at the hematology department in Oncology Center Mansoura University Hospital. A convenient sample of 60 staff nurses were included. Data were collected by a structured interview questionnaire to assess nurses’ knowledge level and observation checklist to assess nurses’ practices pre, and post-blood transfusion training. Data were analyzed by using both descriptive and inferential statistics. Results: Revealed a highly statistically significant difference in the mean score of the nurses’ knowledge level and practice about safe blood transfusion pre and post the training intervention (p=0.001). There was a strong positive relation between nurses’ knowledge and practices scores post-training (r=0.745, P<0.000). Otherwise, it was observed that there was no correlation in the nurse’s knowledge or practice with age and years of experience. Data were presented using tables and charts. Conclusion: Training module on safety blood transfusion can positively improve nurses’ level of knowledge and practice. Recommendation: Ongoing in-service training to nurses at hematology units are essential to improve their knowledge and practice level. Evidence-based practices for blood transfusion should be integrated into the nursing curriculum.